Physical Activity in Overweight and Obese Women: Association with Body Mass Index and Demographic Characteristics - Mahdavi, Reza; Nikniaz, Zeinab; Ostadrahimi, Alireza; Nikniaz, Leila (Applied Research in Quality of Life, 2014)
The aim of present study was determination of the level of physical activity in overweight and obese women and its association with body mass index and various socio-demographic characteristics. In the present cross-sectional survey, the translated and validated form of International physical activity questionnaire was completed by 300 overweight and obese women from Iran-Tabriz. For each activity level, the MET-time value was calculated. The weight and height of subjects were measured and the BMI was calculated. In addition, subjects were asked to indicate their age, marital and socioeconomic status (including employment, educational status, salaries and material endowments) using a general information questionnaire. The One-way ANOVA, Independent t -test, multiple linear regression analysis were used for statistical analysis. Approximately, 45 % of women were physically inactive. Overweight women were more likely to be physically active as compared to obese, while the lowest physical activity rates were observed in older participants. With increasing age, the time spent in vigorous physical activity declined significantly ( p -value = 0.004). Physically active women had higher Socio-economic status. The average time spent on vigorous physical activities were significantly more in single than married women ( p -value < 0.001). Considering the high level of inactivity among studied women, intensive public health efforts together with providing facilities within neighborhoods, are needed to improve women participation in physical activities.